Fiction or facts: Hikayat Merong Mahawangsa (The Kedah Annals) in the view of current civilization value / Dr. Arba'iyah Ab. Aziz ... [et al.] - Ab. Aziz, Arba'iyah; Abdullah, Fadilah; Wan Omar, Wan Noor Faizah; Anuar, Azyyati; Abdul Rahman, Firdaus; Hassan, Hasnira (Universiti Teknologi MARA, 2016)
Hikayat Merong Mahawangsa is a historical document about the writing of ancient Malay folklore, which mirrors the fine Malay traditional culture through the practice of high cultural moral values and customs. The essence of its contents explains that ancient/old Malay culture is rich with values which can be learned and taken as an example. The genealogy of Malay rulers have been previously analysed and discussed by scholars from different era. The translation of this account tells about its very own and unique metaphors, myths and legends. It is known that almost all ancient Malay kingdoms are connected to a particular history about their origins and ruling chronicles. Hikayat Merong Mahawangsa is the truth as well as a literary document to prove that the Malay history cannot be denied and its significance need to be understood. Thus, among the objectives of this paper work is to see whether Hikayat Merong Mahawangsa is a fictional or a factual account. Apart from that, this paper is meant to investigate whether the work is still relevant with the values of Malay modern society.